The CTSA Consortium's Catalog of Assets for Translational and Clinical Health Research (CATCHR) - Jana Shirey‐Rice; Brandy Mapes; Melissa Basford; Anneliese Zufelt; Firas Wehbe; Paul Harris; Michael Alcorn; David Allen; Margaret Arnim; Susan Autry; Michael S. Briggs; Andrea Carnegie; et al. (Wiley, 2014)
Abstract The 61 CTSA Consortium sites are home to valuable programs and infrastructure supporting translational science and all are charged with ensuring that such investments translate quickly to improved clinical care. Catalog of Assets for Translational and Clinical Health Research (CATCHR) is the Consortium's effort to collect and make available information on programs and resources to maximize efficiency and facilitate collaborations. By capturing information on a broad range of assets supporting the entire clinical and translational research spectrum, CATCHR aims to provide the necessary infrastructure and processes to establish and maintain an open‐access, searchable database of consortium resources to support multisite clinical and translational research studies. Data are collected using rigorous, defined methods, with the resulting information made visible through an integrated, searchable Web‐based tool. Additional easy‐to‐use Web tools assist resource owners in validating and updating resource information over time. In this paper, we discuss the design and scope of the project, data collection methods, current results, and future plans for development and sustainability. With increasing pressure on research programs to avoid redundancy, CATCHR aims to make available information on programs and core facilities to maximize efficient use of resources.